PENGARUH MEDIA IKLAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK PERUMAHAN PT. ASTA KARYA (KASUS HUNIAN PERUMAHAN ASTAM HOUSE PEKANBARU) - Suharwanto, bnu; Andri, Seno (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Consumer decision differentiated by pursuant to information seeking and problem recognition. Each;Every marketing communications interaction provide data which is more amount mengani itself marketing and consumer. Consumer will tend to to feel better hit themselves if they if given by the information better and given by a road;street for the the information. Marketing without beriklan as a having good product but have never on the market to buyer. PT Asta Karya is a take careing property residing in pekanbaru standing from year 2009, as for this address PT Asta Karya located in faculty UIN Panam front. In develop;building housing PT Asta Karya only develop;build housing Astam House which is located in Great road;street Kubang of Pekanbaru, in do/conduct advertisement activity, PT Asta Karya in introducing housing Astam House use some advertisement media, that is by using electronic media of like advertising it in media print, external media of column of like advertisement board installation Billboard, and the brochure media. In expecting with directional marketing concept, promotion can be run better.This research is done/conducted at komplek of Housing of Astam House Jl. Great of Kubang Pekanbaru. population as much 83. Writer make all population as responder by using method of unrightious sensus,sementara of head and employees function as fasilitator giving data of supporter in this research. In this research is methodologies used by is quantitative and descriptive with program SPSS, Technics of data collecting of through interview, observation and kuesioner.From hasilanalisis of data which meliputiujivaliditas, reabilitas, linear danregresi modestly, that contribution of influence of variable of media of advertisement to variable of decision of buy is equal to 51,1%, while the rest of equal to 48,9 % influenced by other;dissimilar variable is which is not packed into by this model, is Inferential, Assess t count/calculate > t of[is tables of ( 9,205 > 1,990) and Signifikansi < 0,05 ( 0,000 < 0,05). Signifikansi < 0,05 Hence Ho refused and [Is] ha accepted. become can be said that by media of advertisement have an effect on signifikan to decision of consumer buy